The Relationship Between Binocular Visual Field Loss and Various Stages of Monocular Visual Field Damage in Glaucoma Patients. Issue 1 (January 2019) - Xu, Jianan; Lu, Peng; Dai, Miaomiao; Huang, Wenmin; Lin, Jialiu; Huang, Jingjing
Abstract : Purpose: To investigate the effects of monocular visual field loss severity on binocular visual field (BVF) loss in primary angle-closure glaucoma, primary open-angle glaucoma, and normal tension glaucoma patients. Materials and Methods: In this observational cross-sectional study, 250 glaucoma patients and 31 healthy participants were assigned to groups according to the stage of monocular visual field loss in both eyes; normal, early, moderate, or severe. BVF assessments were determined via integrated visual field and Esterman binocular visual evaluations. Monocular and BVF parameters were compared within and among groups. Results: In patients with one eye at normal or early stage and the other at severe stage, the average integrated mean deviations (MDs) were [mean (SD)], −1.67 (1.39), and −3.27 (2.05) dB, respectively, and the average Esterman scores were >95% [99.17% (1.89%), 96.08% (3.99%), respectively]. Where both eyes had progressed to moderate or severe damage (moderate/moderate, moderate/severe, or severe/severe), the average integrated MDs were worse than −6 dB, and the mean Esterman scores in the moderate/moderate and the moderate/severe damage groups were still >90% [94.20% (5.96%), 94.32% (4.95%), respectively], but it dropped rapidly from >90% to 68.44% (26.27%) when both eyes were at severe stage. Conclusions: The BVF can remain relatively intact provided one eye is at the normal or early stage. Significant BVF defects measured by integrated MD were evident when both eyes had progressed to moderate or severe stage, and significant Esterman BVF defects were only detected when both eyes had advanced to a severe stage.